STRATEGI KOMUNIKASI ORGANISASI PESANTREN DALAM MELIBATKAN ALUMNI UNTUK MEMPROMOSIKAN PONDOK PESANTREN NURUL QUR’AN PRAYA LOMBOK TENGAH - ENDANG RAHMAWATI; WENI ARIANA (TASÂMUH, 2021)
Seeing the increasingly diverse competitiveness of Islamic boarding schools because the number of Islamic boarding schools continues to increase every year, for this reason, Nurul Quran Islamic Boarding School also has a strategy in promoting its Islamic boarding schools. This study aims to find out how the communication strategy of Islamic boarding schools in involving alumni to promote Nurul Quran Islamic boarding schools and what alumni do in promoting Islamic boarding schools. The approach used in this research is modern organizational communication theory and qualitative research methods with data collection techniques of observation, interviews and documentation. as for the subject of this research is the Organization of the Nurul Qur'an Islamic Boarding School. The results of this study indicate that the pesantren's communication strategy in involving alumni to promote the boarding school is to form Jami;ah or ILMINA management groups, Alumni maintain good relations with the pesantren, build good communication between alumni, create ILMINA social media accounts, participate in activities cottage. then the alumni in promoting the cottage, namely by following the social media accounts of the cottage and ILMINA administrators on the social media of each alumni, holding special alumni events at the cottage and outside the cottage.